Do financial market frictions hurt the performance of women‐led ventures? A meta‐analytic investigation - Ross, David Gaddis; Shin, Dong Hyun (Strategic Management Journal, 2024)
Abstract Research Summary Extant research offers conflicting views about the size and nature of gender‐related disparities in venture financing and venture performance. We theorize that gender‐related frictions in debt financing, the most common source of capital for new ventures, materially impair the performance of women‐led ventures but that these frictions decline with financial development. We find strong support for these predictions in a meta‐analysis of 63 primary studies in which we use financial development to instrument for the impact of gender‐related financial frictions on venture performance; in fact, in the absence of gender‐related financial frictions, ventures led by women would modestly outperform ventures led by men. We also find that gender‐related financial frictions are greater for access to, than the terms of, debt financing. Managerial Summary We use meta‐analysis to offer a quantitative synthesis of the research on gender, venture finance, and venture performance. We find evidence that women encounter gender‐related frictions in obtaining debt financing for their ventures, materially impairing their ventures' performance. In fact, in the absence of these frictions, ventures led by women would modestly outperform ventures led by men. We also find that gender‐related frictions in venture finance are greater for access to, than the terms of, debt financing and that these frictions tend to be stronger in countries with less developed financial institutions and markets.